PENGARUH PELATIHAN BANTUAN HIDUP DASAR (BHD) TERHADAP PENGETAHUAN DRIVER WISATA DI UNITED BALI DRIVER (UBD) DALAM MEMBERIKAN PERTOLONGAN PADA KEGAWATDARURATAN WISATA - Sang Putu Sipo Adnyana; I Gusti Ngurah Juniartha; Meril Valentine Manangkot (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Tourism industry development by increasing number of tourist arrivals each year. There are a lot of tourism emergency caused by tourism industry development, so that important for tourist drivers to know how to administer BLS. The aimed of this study is to determine the effect of BLS training on tourist drivers knowledge at UBD in providing assistance to tourism emergency. Design of this study is a pre-experiment with one group pre-test and post-test. Amounted 37 tourist drivers who are the members of UBD organization used the samples in this study and were selected using purposive sampling technique. The intervention that given is providing BLS training in two sessions for 1 hour every 1 time a meeting given by a certified trainers. Knowledge data collected by a questionnaire. The Wilcoxon test used to analized bivariate data (95% CI; ?=0.05). That are enhancement in knowledge score of tourist drivers after BLS training in the results of this study (p=0,001; p?0.05). Its represented that are an effect of providing BLS training on tourist drivers knowledge in UBD. Researchers recommend to conduct regular BLS training for tourist drivers in UBD.